A Purinergic P2 Receptor Family-Mediated Increase in Thrombospondin-1 Bolsters Synaptic Density and Epileptic Seizure Activity in the Amygdala-Kindling Rat Model - Sun, Hongliu; Ma, Luyu; Zhang, Yurong; Pan, Xiaohong; Wang, Chaoyun; Zhang, Jinjin; Zhang, Xiuli; Sun, Hongwei; Wang, Qiaoyun; Zhu, Wei (Frontiers in Cellular Neuroscience, 2018)
Previous studies suggested that the thrombospondin-1/transforming growth factor-β1 (TSP-1/TGF-β1) pathway might be critical in synaptogenesis during development and that the purinergic P2 receptor family could regulate synaptogenesis by modulating TSP-1 signaling. However, it is unclear whether this pathway plays a role in synaptogenesis during epileptic progression. This study was designed to investigate this question by analyzing the dynamic changes and effects of TSP-1 levels on the density of synaptic markers that are related to epileptic seizure activity. In addition, we evaluated whether P2-type receptors could regulate these effects. We generated a rat seizure model via amygdala kindling and inhibited TSP-1 activity using small interfering RNA (siRNA) interference and pharmacological inhibition. We treated the rats with antagonists of P2 or P2Y receptors, pyridoxalphosphate-6-azophenyl-2’,4’-disulfonic (PPADS) or Reactive Blue 2. Following this, we quantified TSP-1 and TGF-β1 immunoreactivity (IR), the density of synaptic markers, and seizure activity. There were significantly more synapses/excitatory synapses in several brain regions, such as the hippocampus, which were associated with progressing epileptic discharges after kindling. These were associated with increased TSP-1 and TGF-β1-IR. Genetic or pharmacologic inhibition of TSP-1 significantly reduced the density of synaptic/excitatory synaptic markers and inhibited the generalization of focal epilepsy. The administration of PPADS or Reactive Blue 2 attenuated the increase in TSP-1-IR and the increase in the density of synaptic markers that follows kindling and abolished most of the epileptic seizure activity. Altogether, our results indicate that the TSP-1/TGF-β1 pathway and its regulation by P2, particularly P2Y-type receptors, may be a critical promoter of synaptogenesis during the progression of epilepsy. Therefore, components of this pathway may be targets for novel antiepileptic drug development.